Vulnerabilidad sísmica de puentes en Colombia y estrategias para rehabilitación - Yamin, Luis E.; Ruiz, Daniel (Revista de Ingeniería, 2001)
A general diagnosis concerning the seismic vulnerability of the bridges in the main Network of Roads in Colombia is presented based upon approximate appraisals. For those bridges identified as critical in this appraisal, a detailed methodology is presented to evaluate the seismic vulnerability considering simultaneously the problems of load capacity and residual useful life of the bridges due to the large increase of truckload in relation with the original design loads. General criteria are given to define alternatives of rehabilitation and/or reinforcement as well as general guidelines in order to choose the best solution.